EFEK EKSTRAK MELON (Cucumis melo) dan GliadinTERHADAP KADAR Hb DAN HbCO TIKUS WISTAR JANTAN YANG DIPAPAR ASAP ROKOK - Yuyun Erlina Susanti; Bambang Wirjatmadi (Universitas Airlangga, 2016)
The exposure of cigarette smoke produce CO bond in hemoglobin. Melon (Cucumis melo) and gliadin contains of antioxidants that prevent tissue damage. The aim of this study was to analyze the difference of hemoglobin and carboxyhemoglobin concentration in male Wistar rats were exposed to cigarette smoke and had been treated melon extract (Cucumis melo) and gliadin. The study was a laboratory experimental design, using Post Test Control Group Design Research and RAL method (Complete Randomize Design). The sample in this study were 25 male Wistar rats aged 3 months. The research was divided into 5 groups with 5 different treatment : control group, the treatment group were given exposure to cigarette smoke, the treatment group were given of cigarette smoke exposure and melon extract (Cucumis melo) and gliadin dose of 3 IU / day, 4.5 IU / day, and 9 IU / day.The subject were divided into 5 groups each treated for 28 day. The sample size used Federer formula. The collection of data was obtained from the results of laboratory tests to hemoglobin and Carboxyhemoglobin. Hb and HbCO data collected and analyzed by Manova test at 95% confidence level. The results showed significant difference in average Hb and HbCO concentration (p-value = 0.000) between male Wistar rats treated and not treated with melon extract (Cucumis melo) and gliadin. Melon extract has an effect on the decline of HbCO concentration due to exposure to cigarette smoke.Keywords:smoke, melon extract, Hb, HbCO